Synthetic grinding stone, synthetic grinding stone assembly, and method for manufacturing synthetic grinding stone

By adjusting the abrasive particle rate, binder rate and porosity in the synthetic grinding stone, a synthetic grinding stone with excellent processing properties and low friction heat is formed, which solves the problems of reduced processing efficiency and excessive friction heat caused by abrasive particles falling off in dry mirror processing, and achieves an efficient and low-damage surface processing effect.

CN117415736BActive Publication Date: 2025-03-28TOKYO DIAMOND KOGU
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310868375.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-08-31
Filing Date
2023-07-14
Publication Date
2025-03-28
Estimated Expiration
2043-07-14

AI Technical Summary

Technical Problem

During dry mirror processing, the working surface of the synthetic grinding stone becomes smooth, and the abrasive particles fall off, resulting in a reduced contact pressure, reduced processing efficiency, and may lead to burning or scratching of the grinded object.

Method used

A synthetic grinding stone with abrasive particle ratio (Vg) greater than 0 volume % and 40 volume % or less, a nonwoven bond with a binder of 35 volume % or more and less than 90 volume % and a porosity (Vp) greater than 10 volume % and 55 volume % or less, a synthetic grinding stone with excellent processability and low friction heat is formed by adjusting the volume ratio of these parameters.

Benefits of technology

It effectively suppresses excessive friction heat between the synthetic grinding stone and the grinding object, improves processing efficiency, prevents burning and scratching of the grinding object, and achieves a flatter mirror processing effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117415736B_ABST
    Figure CN117415736B_ABST
Patent Text Reader

Abstract

The synthetic grinding stone for surface processing comprises: abrasive grains having a grinding grain ratio (Vg) greater than 0 volume % and less than 40 volume % and a non-woven fabric binder having a binder ratio (Vb) greater than 35 volume % and less than 90 volume %. Furthermore, the porosity (Vp) of the synthetic grinding stone is greater than 10 volume % and less than 55 volume %.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a synthetic grindstone, a synthetic grindstone assembly, and a method for manufacturing the synthetic grindstone for use in surface processing such as chemical mechanical grinding (CMG). Background Art

[0002] Sometimes, a surface processing method based on dry chemical mechanical grinding (CMG) is used (for example, refer to Japanese Patent Gazette No. 4573492). In the CMG process, a synthetic grindstone with an abrasive (abrasive grains) fixed by a resin binder such as a thermoplastic resin is used. Then, while the wafer and the synthetic grindstone are rotated, the synthetic grindstone is pressed against the wafer (for example, refer to Japanese Patent Gazette No. 2004-87912). The convex parts of the wafer surface are heated / oxidized by friction with the synthetic grindstone, and become brittle and peel off. As a result, only the convex parts of the wafer are ground and flattened. Summary of the invention

[0003] For synthetic grindstones, for example, as the CMG process proceeds, abrasive grains (abrasives) gradually fall off from the surface of the synthetic grindstone's binder (mirror-finished working surface) facing the object to be grinded, and the working surface of the synthetic grindstone becomes smooth. Therefore, on the working surface, for example, the contact opportunity between the thermoplastic resin-based binder and the object to be grinded increases. As a result, the contact pressure between the abrasive grains and the object to be grinded decreases, and the processing efficiency decreases. On the other hand, when dry processing is performed to increase the processing rate, the friction heat between the working surface of the synthetic grindstone and the object to be grinded becomes too large, and there is a possibility that the object to be grinded will be burned or scratched due to the inclusion of grinding residues.

[0004] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a synthetic grindstone, a synthetic grindstone assembly, and a method for manufacturing a synthetic grindstone that can suppress excessive generation of frictional heat, for example, during dry mirror finishing.

[0005] Solutions to the problem

[0006] A synthetic grinding stone for surface processing according to one embodiment of the present invention comprises abrasive grains having a grinding grain ratio (Vg) greater than 0 volume % and less than 40 volume % and a nonwoven fabric binder having a binder ratio (Vb) greater than 35 volume % and less than 90 volume %. The synthetic grinding stone has a porosity (Vp) greater than 10 volume % and less than 55 volume %. BRIEF DESCRIPTION OF THE DRAWINGS

[0007] Figure 1 Schematic diagram of the structure of the synthetic grindstone according to the embodiment.

[0008] Figure 2 It is a schematic diagram showing the production flow (production method) of a synthetic grindstone (molded body).

[0009] Figure 3 This is a ternary diagram showing three elements (abrasive grain ratio (Vg), binder ratio (Vb), and porosity (Vp)) of a synthetic grinding stone when a nonwoven fabric type synthetic grinding stone is produced.

[0010] Figure 4 is with Figure 3 The hardness values ​​of the synthetic grinding stone corresponding to each point.

[0011] Figure 5 Is it possible to manufacture Figure 3 Schematic diagram of the boundary of a nonwoven type synthetic grindstone is shown.

[0012] Figure 6 This is an image of a synthetic grinding stone that can withstand use magnified 1500 times.

[0013] Figure 7 Schematic diagram showing a CMG device used for machining a workpiece.

[0014] Explanation of symbols

[0015] 10···CMG device, 43···grindstone holding member, 100···synthetic grindstone, 101···abrasive grains, 102···binder, 200···synthetic grindstone assembly. DETAILED DESCRIPTION

[0016] like Figure 1 As shown, the synthetic grindstone 100 is formed of abrasive grains (abrasive) 101 and a binder (adhesive) 102. The synthetic grindstone 100 may further have pores 103. In the present embodiment, the synthetic grindstone 100 is arranged such that the abrasive grains 101 are dispersed in the binder 102 and the pores 103 are dispersed in the binder 102.

[0017] The abrasive grains 101 are not limited to the following materials. When the object to be ground is silicon, for example, silicon dioxide, cerium oxide, or a mixture thereof can be appropriately applied. Similarly, when the object to be ground is sapphire, chromium oxide, iron oxide, or a mixture thereof can be appropriately applied. In addition, as abrasives that may be applied, aluminum oxide, silicon carbide, or a mixture thereof can also be used depending on the type of the object to be ground.

[0018] In this embodiment, the grinding object is silicon, and cerium oxide having an average particle size of about 1 μm is used as the abrasive grains 101. The particle size of the abrasive grains 101 can be appropriately set, and is preferably less than 5 μm, for example.

[0019] In this embodiment, nonwoven fabric is used as the binder 102. As an example of the nonwoven fabric, polyester staple fibers can be used. As the polyester staple fibers, for example, polyethylene terephthalate (PET) staple fibers can be used.

[0020] Synthetic grinding stone (molded body) 100 based on Figure 2 First, Figure 3 Abrasive grains 101 of the volume ratio described below and a short fiber-shaped binder 102 for forming a nonwoven fabric are mixed to obtain a mixed material (mixed powder) (step ST1). The binder 102 is substantially in a powdery state when viewed without magnification.

[0021] Next, the mixed material is filled into a mold for forming the final shape of the synthetic grinding stone 100 (step ST2). At this time, the fibers may be gathered by a dry method, a wet method, or other methods. For example, the synthetic grinding stone 100 is molded into a molded body by press molding (hot pressing) at 170° C. for 30 minutes (step ST3). Then, the molded body in the mold is demolded (step ST4).

[0022] Figure 3 3 shows a ternary diagram of the so-called three elements (abrasive grain ratio (Vg), binder ratio (Vb), and porosity (Vp)) of the synthetic grinding stone 100 when the nonwoven fabric type synthetic grinding stone 100 is manufactured as described above.

[0023] Figures 3 to 5 The results of an experiment (19 points) of manufacturing a synthetic grinding stone 100 by appropriately adjusting the three elements of the synthetic grinding stone 100 (abrasive grain ratio (Vg), binder ratio (Vb), and porosity (Vp)) are shown in FIG. This experiment formed a boundary between the possibility of manufacturing a synthetic grinding stone 100 and the impossibility of manufacturing a synthetic grinding stone 100. Figure 5 In the case of a composition inside the illustrated boundary, it can be used as a synthetic grindstone 100 .

[0024] Of the 19 points, 13 points formed the synthetic grindstone 100 that could endure the use. The range of these 13 points is that the abrasive grain ratio (Vg) of the abrasive grains is in the range of 0 volume % or more and 40 volume % or less, the binder ratio (Vb) is in the range of 35 volume % or more and less than 90 volume %, and the porosity (Vp) of the pores is greater than 10 volume % and less than 55 volume %. Figure 3 to Figure 5, even when the abrasive grain rate is 0 volume %, the synthetic grindstone 100 is formed. When the abrasive grain rate is 0 volume %, the synthetic grindstone 100 does not contain the abrasive grains 101, so the abrasive grain rate of the synthetic grindstone 100 is actually greater than 0 volume %. In this embodiment, for the synthetic grindstone 100, the abrasive grain rate (Vg) of the grindstone 101 is determined first, and then the binder rate (Vb) of the binder 102 is set.

[0025] Figure 6 FIG. 1 shows an image of one of the synthetic grinding stones 100 that can withstand use at 13 points, magnified 1500 times using a scanning electron microscope. Figure 6 The nonwoven fabric binder 102 was confirmed in the synthetic grindstone 100. Figure 6 In the figure, fibrous resin (elongated pattern) of the nonwoven fabric as the binder 102 and particulate abrasive grains 101 attached to the fibrous resin were confirmed.

[0026] Shore hardness measurement (ASTM D2240-05 Type DO) was performed on 13 points that can be used as the synthetic grindstone 100 . Figure 4 It is shown in Figure 3 The hardness of the synthetic grinding stone 100 at each point corresponds to the hardness of the synthetic grinding stone 100 at each point. Figure 3 to Figure 5 As shown in the figure, when the porosity increases, the synthetic grindstone 100 becomes softer, and when the porosity decreases, it becomes harder.

[0027] It should be noted that, hereinafter, the six points where the synthetic grinding stone 100 cannot be formed are referred to as molded bodies. Figure 5 The composition outside the boundary shown is that the remaining 6 points among the 19 points are molded bodies that cannot form the synthetic grinding stone 100. In the area of ​​arrow α, Figure 5 The molded body outside the boundary shown has a high porosity and a low packing density. Therefore, the bonding of the binder to the molded body is insufficient, which can be considered to be the result of severe disintegration such as the corners and surface of the molded body being broken. In the area of ​​arrow β, Figure 5 The porosity of the molded body outside the boundary shown is low and the packing density is sufficient. However, the binder ratio is low and it is assumed that the surface of the molded body has become powdery. In the area of ​​arrow γ, it is assumed that Figure 5 The porosity of the molded body outside the boundary shown is too low and the packing density is too high, resulting in that the molded body cannot reach the predetermined size during molding.

[0028] It is conceivable that when the abrasive grain rate is too high, the molded body will collapse without bonding. As described above, the abrasive grain rate is preferably greater than 0 volume % and not more than 40 volume %, for example.

[0029] It is understood from this that only by setting the abrasive grain ratio, binder ratio, and porosity to a predetermined range of volume ratios can the synthetic grindstone 100 using nonwoven fabric as a binder be molded.

[0030] In this embodiment, the synthetic grindstone 100 is formed in a disk shape and is used for dry chemical mechanical grinding (CMG) processing that performs processing by a mechanical action and a combined action based on chemical components. That is, the synthetic grindstone 100 performs a chemical mechanical grinding action on the surface of the wafer W as the object to be grinded in a dry manner, thereby performing surface processing of the wafer W as the object to be grinded. Then, the synthetic grindstone 100 is fixed to the grindstone holding member (base) 43 by double-sided tape, adhesive, etc., to form a synthetic grindstone assembly 200, which is installed in Figure 7 The CMG device 10 shown is used for surface processing of a wafer W as a grinding object. The grindstone holding member 43 only needs to have appropriate rigidity to withstand CMG processing, be heat-resistant at a temperature that rises due to the use of the synthetic grindstone 100, and not be thermally softened, and can be made of, for example, an aluminum alloy material.

[0031] The synthetic grindstone assembly 200 including the grindstone holding member 43 and the synthetic grindstone 100 and the wafer W as the object to be grinded are moved along the Figure 7 The wafer W is pressed against the synthetic grindstone 100 while rotating in the direction of the arrow in FIG. 1. At this time, the synthetic grindstone 100 is rotated at a peripheral speed of, for example, 600 m / min, and the processing pressure is 300 g / cm 2 The wafer W is pressed. Therefore, the synthetic grindstone 100 slides on the surface of the wafer W. When the processing is started in this way, the synthetic grindstone 100 slides on the surface of the wafer W, and an external force acts on the binder 102. This external force acts continuously, and as the CMG process proceeds, the abrasive grains (abrasive) gradually fall off from the surface (mirror-finished working surface) of the binder 102 of the synthetic grindstone 100 that is opposite to the surface of the wafer W to be ground. Then, the surface of the wafer W is polished by the chemical mechanical action of the fixed abrasive grains 101 retained in the non-woven fabric as the binder 102 or the abrasive grains 101 that fall off from the non-woven fabric as the binder 102. The convex parts on the surface of the wafer W are heated / oxidized by the friction with the synthetic grindstone 100, and become brittle and peel off. As a result, only the convex parts on the surface of the wafer W are ground, and the surface of the wafer W is flattened.

[0032] In the present embodiment, a thermoplastic resin material (e.g., ethyl cellulose) is not used as a binder, but a nonwoven fabric is used as the binder 102. Therefore, compared with the case where a thermoplastic resin material is used as a binder, the elastic deformation amount of the binder 102 can be further increased. Therefore, the synthetic grindstone 100 of the present embodiment has excellent followability to the surface of the wafer W as the object to be ground (workpiece).

[0033] When a thermoplastic resin material is used as a binder, when heat is accumulated between the synthetic grindstone and the wafer W, the thermoplastic resin material as a binder softens, causing dissolution on the surface of the synthetic grindstone, etc. Furthermore, when the thermoplastic resin material as a binder melts and is welded to the surface of the wafer W in a process called sticking, the grinding resistance generated by the synthetic grindstone increases sharply, causing the surface of the wafer W to become rough and scratched.

[0034] In contrast, when a nonwoven fabric is used as the binder 102 as in the synthetic grindstone 100 of the present embodiment, even if heat is stored in the binder 102, dissolution does not occur on the surface of the synthetic grindstone 100. Therefore, even if heat is stored between the synthetic grindstone 100 and the wafer W, the binder 102 can be prevented from melting. Therefore, the synthetic grindstone 100 of the present embodiment can maintain stable processing performance for a longer period of time. Therefore, it is possible to prevent accidental scratches from being generated on the surface of the wafer W as the object to be grinded. Therefore, by using the binder 102 made of nonwoven fabric of the present embodiment, the object to be grinded (the surface to be processed) can be ground more flexibly than when a thermoplastic resin material is used as the binder, which can contribute to reducing damage to the object to be grinded.

[0035] This is because the inventors of the present application, who have conducted intensive research to improve the excessive generation of frictional heat during dry mirror finishing, have found that by forming the synthetic grindstone 100 in a manner that satisfies the three elements of a grindstone in the above-mentioned three-phase diagram, it is possible to achieve excellent workability on the object to be grinded. That is, for example, the synthetic grindstone 100 suitable for dry surface finishing includes abrasive grains 101 having an abrasive grain ratio (Vg) greater than 0 volume % and less than 40 volume %, and a binder 102 made of nonwoven fabric having a binder ratio (Vb) greater than 35 volume % and less than 90 volume %, and the porosity (Vp) of the synthetic grindstone 100 is greater than 10 volume % and less than 55 volume %. By using the synthetic grindstone 100 of this embodiment, when dry mirror finishing is performed, for example, it is possible to utilize the chemical solid phase reaction caused by the high temperature and high pressure locally generated between the synthetic grindstone 100 and the object to be grinded, and suppress the excessive generation of frictional heat between the synthetic grindstone 100 and the object to be grinded. Furthermore, when the object to be ground is mirror-finished by, for example, a dry process using the synthetic grindstone 100 of the present embodiment, it is possible to achieve extremely flat processing (mirror-finishing) of the surface roughness of the object to be ground, for example, at a sub-nm level.

[0036] According to the present embodiment, it is possible to provide the synthetic grindstone 100 , the synthetic grindstone assembly 200 , and the method for manufacturing the synthetic grindstone 100 , which can suppress excessive generation of frictional heat during dry mirror finishing, for example.

[0037] In the present embodiment, the range that can be formed into the synthetic grindstone 100 is set for the example of the nonwoven fabric using PET short fibers as the binder 102. In addition to polyester short fibers, polyamide (PA) short fibers or polypropylene (PP) short fibers can also be used as the nonwoven fabric of the binder 102. It should be noted that as the nonwoven fabric, one or more of polyester short fibers, polyamide (PA) short fibers and polypropylene (PP) short fibers can be selected. Moreover, when these nonwoven fabrics are used as the binder 102, the range of the volume ratio of the above-mentioned abrasive grain rate (Vg), binder rate (Vb), and porosity (Vp) can also be set in the same way as when using PET short fibers. It should be noted that the nonwoven fabric used as the binder 102 is not limited to this. For example, a long-fiber nonwoven fabric can be used. As the long-fiber nonwoven fabric, polyester long fibers, polypropylene long fibers, etc., or a mixture thereof can be used.

[0038] It should be noted that the short fiber nonwoven fabric refers to a nonwoven fabric made of a material obtained by cutting fibers, and the long fiber nonwoven fabric refers to a nonwoven fabric made of a material obtained by connecting fibers in an endless manner. The short fiber nonwoven fabric uses cut fibers, and the fiber length of the short fiber nonwoven fabric can be appropriately set. An example of the fiber length of the short fiber nonwoven fabric is micron-level. In addition, the long fiber nonwoven fabric is, for example, fibers connected together with the same length as the winding length. For example, if there is a winding of 100m, one fiber is about 100m.

[0039] In this embodiment, an example in which the synthetic grindstone 100 is provided in a disk shape is described. The synthetic grindstone 100 may be formed in various shapes such as a granular shape or an elongated rectangular parallelepiped shape. The synthetic grindstone assembly 200 may be formed in an appropriate shape so as to hold the synthetic grindstone 100 .

[0040] Although the synthetic grindstone 100 of the present embodiment is described as an example in which dry machining is used, the synthetic grindstone 100 may be used for wet machining using grinding water (for example, pure water), for example.

[0041] (First Modification)

[0042] A case where the synthetic grindstone 100 according to the present modification includes coarse particles of an appropriate size as the first filler will be described.

[0043] The first filler is preferably spherical, for example, but is not necessarily limited to a sphere, and may be block-shaped and may include a small amount of concavo-convex or deformation. The first filler is, for example, silica, which is dispersed and fixed by a binder 102 made of a non-woven fabric. The first filler preferably includes silica having a larger particle size than the particle size of the abrasive grains 101, and silica having a smaller particle size fixed around the silica having a larger particle size. The silica having a smaller particle size is preferably smaller than the particle size of the abrasive grains 101. The volume ratio of the first filler in the synthetic grindstone 100 can be set, for example, based on the abrasive grain rate (Vg) of the abrasive grains 101 and according to the correlation with the binder rate (Vb) of the binder 102. That is, in this modified example, for the synthetic grindstone 100, the abrasive grain rate (Vg) of the abrasive grains 101 is first determined, and then the binder rate (Vb) of the binder 102 and the volume ratio of the first filler are set according to the correlation between the binder 102 and the first filler. The first filler content is preferably more than 0 volume % and 40 volume % or less.

[0044] It should be noted that the abrasive grains 101 formed of cerium oxide are of equal or softer quality than the wafer W or its oxide, which is the object to be ground and has silicon as the main component. In addition, the first filler formed of silicon dioxide is of equal or softer quality than the wafer W or its oxide, which is the object to be ground.

[0045] The synthetic grindstone 100 including the abrasive grains 101 , the nonwoven fabric binder 102 , and the first filler is manufactured as described in the above embodiment.

[0046] The average particle size of the first filler is larger than that of the abrasive grains 101, so the synthetic grindstone 100 and the wafer W being processed are in contact with each other substantially through the apex of the first filler. That is, between the base material (abrasive grains 101 and the nonwoven fabric binder 102) of the synthetic grindstone 100 and the wafer W, the base material and the wafer W are not in direct contact due to the presence of the first filler, and a certain gap is formed.

[0047] When the processing starts in the state where the first filler is in contact with the wafer W, an external force acts on the base material. The abrasive grains 101 fall off from the base material due to the continuous action of the external force. The free abrasive grains 101 are present at the processing interface in the gap between the synthetic grindstone 100 and the wafer W in the state of being attached to the first filler. Therefore, the abrasive grains 101 being processed and the wafer W are basically in contact through the apex of the first filler. Therefore, the actual contact area between the abrasive grains 101 and the wafer W is greatly reduced, and the acting pressure at the processing point is increased. Therefore, grinding processing can be performed with high processing efficiency.

[0048] The gap promotes the circulation between the surface of the wafer W and the outside atmosphere, and the processed surface is cooled. In addition, the residue generated by the abrasive grains 101 is discharged from the wafer W to the outside through the gap, and the surface of the wafer W can be prevented from being damaged. As a result, the surface of the wafer W can be prevented from being burned or scratched due to frictional heat.

[0049] Thus, the synthetic grindstone 100 can grind the surface of the wafer W to be flat and have a predetermined surface roughness.

[0050] According to the synthetic grindstone 100 of this modification, even when machining is performed, the contact pressure between the abrasive grains 101 and the wafer W can be sufficiently maintained to maintain machining efficiency, and by suppressing direct contact between the adhesive 102 and the wafer W, the quality of the wafer W can be prevented from being degraded and scratched. In this modification, as described in the above-mentioned embodiment, it is possible to suppress excessive friction heat generated by the heat generated between the synthetic grindstone 100 and the workpiece.

[0051] As the first filler, silica, carbon, and silica gel as porous bodies thereof, activated carbon, spherical resin, etc. It should be noted that hollow spheres used as pore-forming agents are not suitable because they may break during processing and cause scratches.

[0052] (Second Modification)

[0053] The synthetic grindstone 100 of this modification includes a conductive material as a second filler that is smaller than the first filler described in the first modification and has an appropriate size. In addition, in this modification, an example is described in which the grindstone holding member 43 of the CMG device 10 described above uses, for example, an aluminum alloy material as a raw material having electrical conductivity and appropriate thermal conductivity.

[0054] As the conductive material, carbon nanotubes and the like can be cited. These materials are smaller than the average particle size of the abrasive grains 101. The volume ratio of the second filler in the synthetic grindstone 100 can be set, for example, based on the abrasive grain rate (Vg) of the abrasive grains 101 and according to the correlation with the binder rate (Vb) of the binder 102. That is, in this modification, for the synthetic grindstone 100, the abrasive grain rate (Vg) of the abrasive grains 101 is first determined, and then the binder rate (Vb) of the binder 102 and the volume ratio of the second filler are set according to the correlation between the binder 102 and the second filler. The second filler is preferably added in a range of more than 0 volume % and within 10 volume %. In addition, the second filler can improve the strength of the structure of the synthetic grindstone 100 by using carbon nanotubes, etc., for example.

[0055] When the CMG device 10 starts processing the wafer W, the synthetic grindstone 100 and the wafer W slide, and an external force is applied to the adhesive 102. As the external force continues to act, the abrasive grains 101 fall off. The free abrasive grains 101 slide in the gap between the synthetic grindstone 100 and the wafer W. The surface of the wafer W is polished by the chemical mechanical action of the abrasive grains 101.

[0056] When the surface of the wafer W is polished and rubbed, static electricity is generated on the surface of the wafer W. At this time, the conductive second filler causes the static electricity on the surface of the wafer W to flow to the grindstone holding member 43 (see Figure 7 ). Therefore, by using the synthetic grindstone 100 of this embodiment, static electricity generated on the surface of the wafer W can be removed while grinding the surface of the wafer W. As a result, dust and the like can be prevented from being attached to the surface of the wafer W.

[0057] In addition, in this modification, the thermal conductivity of the grindstone holding member 43 is higher than that of the synthetic grindstone 100. When the surface of the wafer W is ground and friction occurs, friction heat is generated on the surface of the wafer W. At this time, the friction heat is absorbed by the second filler, and the heat absorbed by the second filler is transferred to the grindstone holding member 43. Therefore, by using the synthetic grindstone 100 of this modification, the surface of the wafer W can be ground while the friction heat generated on the surface of the wafer W is removed. As a result, it is possible to prevent the surface of the wafer W from being burned due to the friction heat between the surface of the synthetic grindstone 100 and the surface of the wafer W, and also to prevent scratches. Therefore, the synthetic grindstone 100 of this modification can not only process the surface of the wafer W well, but also extend the life of the synthetic grindstone 100.

[0058] It should be noted that it is also preferable to provide a heat dissipation portion such as a heat sink on the grindstone holding member 43 that rotates together with the synthetic grindstone 100, that is, it is preferable that the synthetic grindstone assembly 200 has a heat dissipation portion (heat transfer portion). In this case, the heat dissipation portion contacts the air by rotating, and the heat of the synthetic grindstone 100 can be effectively dissipated.

[0059] Furthermore, by providing a water distribution pipe for cooling water or the like inside the grindstone holding member 43 , the grindstone holding member 43 and the synthetic grindstone 100 can also be cooled.

[0060] In this modification, the example in which the grindstone holding member 43 has electrical conductivity and higher thermal conductivity than the synthetic grindstone 100 has been described, but it may be formed of a material having at least one of electrical conductivity and higher thermal conductivity than the synthetic grindstone 100. When it has electrical conductivity, static electricity between the grinded object and the synthetic grindstone 100 can be removed, and when it has higher thermal conductivity than the synthetic grindstone 100, heat generated in the synthetic grindstone 100 can be effectively dissipated.

[0061] In addition, the example using the first filler is described in the first modification, and the example using the second filler is described in the second modification. It is also preferable that the synthetic grindstone 100 includes both the first filler and the second filler.

[0062] (Third Modification)

[0063] A case where the synthetic grindstone 100 of the present modification includes particles of an appropriate size smaller than the first filler described in the first modification as the third filler will be described.

[0064] As the particles of the third filler, green carborundum (GC) and the like can be cited. These particles are harder than the wafer W as the object to be ground. The particles of the third filler such as GC can be larger or smaller than the average particle size of the abrasive grains 101. Of course, the particles of GC and the like can also be of the same size as the average particle size of the abrasive grains 101.

[0065] For example, the average particle size of the abrasive grains 101 of metal oxides such as alumina, zirconia, ceria, and silica can be larger than GC, smaller than GC, or the same as GC. For example, the average particle size of the abrasive grains 101 of alumina, zirconia, and ceria is basically larger than GC. For example, the average particle size of the abrasive grains 101 of alumina can be the same as GC (~200nm). For example, when the particles of GC and the like are 10nm, the average particle size of the abrasive grains 101 of silica and the like can be 1nm. The volume ratio of the third filler in the synthetic grindstone 100 can be set, for example, based on the abrasive grain rate (Vg) of the abrasive grains 101 and according to the correlation with the binder rate (Vb) of the binder 102. The third filler is preferably added in a range of more than 0 volume % and within 10 volume %.

[0066] There is a technique for forming gettering sites such as fine scratches on the back side of the wafer W opposite to the surface and capturing impurities through the gettering sites (gettering effect). GC is harder than the back side of the wafer W and is used to intentionally form scratches on the back side of the wafer W.

[0067] In this modification, as described in the above embodiment, excessive frictional heat generated by heat generated between the synthetic grindstone 100 and the object to be grinded can be suppressed. In addition, if the GC has conductivity, static electricity generated between the synthetic grindstone 100 and the object to be grinded can be suppressed.

[0068] It should be noted that the present invention is not limited to the above-mentioned embodiments, and various modifications can be made in the implementation stage without departing from the scope of the main purpose. In addition, each embodiment can also be implemented in appropriate combination, and in such a case, the effect of the combination can be obtained. In addition, the above-mentioned embodiments include various inventions, and various inventions can be extracted from the combination of multiple constituent elements selected from the disclosure. For example, in the case where the technical problem can be solved and the effect can be obtained even if some constituent elements are deleted from all the constituent elements shown in the embodiment, the structure in which the constituent elements are deleted can be extracted as an invention.

Claims

1. A synthetic grinding stone for surface processing of a grinded object, the synthetic grinding stone comprising: Abrasive grains having a grinding ratio (Vg) of more than 0 volume % and less than 40 volume %, and A binder made of a nonwoven fabric having a binder ratio (Vb) of 35% by volume or more and less than 90% by volume, The porosity (Vp) of the synthetic grinding stone is greater than 10 volume % and less than 55 volume %, The nonwoven fabric binder comprises at least one selected from polyester staple fibers, polyamide staple fibers, and polypropylene staple fibers. The synthetic grinding stone is used for performing the surface processing in a dry manner, The synthetic grindstone includes a first filler having an average particle diameter larger than that of the abrasive grains, and the first filler is not a hollow sphere.

2. A synthetic grinding stone for dry surface processing, the synthetic grinding stone comprising: Abrasive particles, a nonwoven fabric binder for maintaining the abrasive in a dispersed state, and a first filler having an average particle size larger than that of the abrasive grains, The first filler is not a hollow sphere, The nonwoven fabric binder comprises at least one selected from polyester staple fibers, polyamide staple fibers, and polypropylene staple fibers. The binder ratio (Vb) of the nonwoven fabric binder is 35 volume % or more and less than 90 volume %.

3. The synthetic grindstone according to claim 1 or 2, wherein: The synthetic grinding stone includes at least one of a second filler having electrical conductivity and a third filler that is harder than a workpiece. 4 . The synthetic grinding stone according to claim 1 , which performs chemical mechanical grinding on the object to be ground in a dry manner. 5 . The synthetic grinding stone according to claim 3 , which performs chemical mechanical grinding on the object to be ground in a dry manner.

6. A synthetic grinding stone assembly comprising: The synthetic grinding stone according to claim 2 or 3, and A base body to which the synthetic grindstone is fixed and which has at least one of electrical conductivity and thermal conductivity higher than that of the synthetic grindstone.

7. The method for manufacturing the synthetic grinding stone according to claim 1, comprising: Mixing the abrasive grains and the nonwoven fabric binder to obtain a mixed material; Filling the mixed material into a mold and molding it by hot pressing; as well as The molded body after the molding is demolded.

Citation Information

Patent Citations

  • Dry chemical machanical polishing method for substrate, and device used therefor

    JP2004087912A

  • Vitrified grindstone having rough-textured homogeneous structure

    CN112135710A

  • Wafer grinding system and wafer grinding method

    CN112440203A

  • Porous abrasive tool and method for making the same

    CN1589189A

  • Porous abrasive and process for producing the same

    GB1108303A